The Use of Guided Imagery Therapy for Insomnia Prevention in the Elderly: Literature Review - Fitriani, Neneng Kurnia; Susanto, Tantut; Kurdi, Fahruddin (Jurnal Kesehatan Komunitas Indonesia, 2023)
Background: Insomnia is a common disorder among the elderly population. Appropiate of insomnia management will reduce the health risks during treatment. Guided imagery therapy is important to reduce anxiety, muscle contraction, facilitate good sleep, improve sleep quality and prevent insomnia in the elderly. Aim: The purpose of this study was to describe the use of guided imagery therapy for prevention of insomnia in the elderly. Method: Narrative literature review was performed to select article that relate with guided imagery therapy for prevention of insomnia in the elderly using search engines including PubMed, Scopus, Springerlink, Scienderect, and Google Scholar. The analyzed of articles was carried out using four stages based on the PRISMA Flowchart diagram. Results: The results were indicated six of articles that analyzed in this study. Guided imagery therapy is a relaxation technique performed by imagining a peaceful and pleasant scene, event or object to help stimulate the body's natural relaxation response. All of the articles reviewed show that guided imagery can be used as a non-pharmacological therapy in the management of sleep disorders in the elderly because it has been shown to be effective in improving sleep quality and preventing insomnia in the elderly. Conclusion: The applied guided imagery therapy has a significant effect on reducing insomnia in the elderly. Therefore, guided imagery therapy could be used as an intervention to prevent insomnia in the elderly.